Effectiveness of OSS-Based Licensing Services and HR Competency on Public Satisfaction: A Study in Badung Investment Department - Artini, Ketut Anik; Merta, I Ketut; Yusmini, Ni Made (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
This research focused on the Badung Regency Investment and One-Stop Integrated Services with the aim of analyzing the effectiveness of Online Single Submission (OSS)-based licensing services and human resource competency on community satisfaction, using the grand theory of Human Resource Management (HR). The study employs quantitative associative methods and utilizes a questionnaire with a population of 126 and a sample of 56, calculated using the Slovin formula, with four hypotheses. Data analysis was conducted using multiple linear regression with the help of SPSS Version 24. The research findings indicate the following: 1. Service effectiveness has a positive but insignificant effect on community satisfaction at the Investment and One-Stop Integrated Services, Badung Regency. 2. Service effectiveness has a positive and significant effect on human resource competency at the Investment and One-Stop Integrated Services, Badung Regency. 3. Human resource competency has a positive and significant effect on community satisfaction at the Investment and One-Stop Integrated Services of Badung Regency. 4. Human resource competency is able to partially mediate the effect of service effectiveness on community satisfaction at the Investment and One-Stop Integrated Services of Badung Regency. The implications of this research indicate that service effectiveness, human resource competency, and community satisfaction at the Badung Regency Investment and One-Stop Integrated Services are moderate. Furthermore, the study shows that human resource competency can mediate the relationship between service effectiveness and community satisfaction. However, it was also found that service effectiveness had no significant effect, suggesting that further research is needed.